Gated Convolutional Neural Networks for Text Classification - Sun, Jin; Jin, Rize; Ma, Xiaohan; Park, Joon young; Sohn, Kyung ah; Chung, Tae sun (Lecture Notes in Electrical Engineering, 2021)
The popular approach for several natural language processing tasks involves deep neural networks, and in particular, recurrent neural networks (RNNs) and convolutional neural networks (CNNs). While RNNs can capture the dependency in a sequence of arbitrary length, CNNs are suitable for extracting position-invariant features. In this study, a state-of-the-art CNN model incorporating a gate mechanism that is typically used in RNNs, is adapted to text classification tasks. The incorporated gate mechanism allows the CNNs to better select which features or words are relevant for predicting the corresponding class. Through experiments on various large datasets, it was found that the introduction of a gate mechanism into CNNs can improve the accuracy of text classification tasks such as sentiment classification, topic classification, and news categorization.
Keywords: Invariant features; Large datasets; NAtural language processing; Recurrent neural network (RNNs); Sentiment classification; State of the art; Text classification; Topic Classification; Convolutional neural networks; Gate mechanism; Text classification